Seroepidemiological Study of Epstein-Barr Virus in Patients with Head and Neck Tumors at Shahid Rajaee Hospital in Babolsar, Iran - Moslemi, Dariush; Karimi, Masoume; Bijani, Ali; Mostafazadeh, Amrollah; Safiri, Hamid; Mohammadi Nokhandani, Akram; Moslemi, Mohammad (Reports of Radiotherapy and Oncology, 2021)
Background: Epstein-Barr virus (EBV) is a herpes virus, which is the cause of infectious mononucleosis. Seroepidemiological studies show that more than 95% of adults in the world are infected with this virus. This virus is a modifying virus that is associated with some malignancies such as Burkitt lymphoma, tumors in HIV-infected patients, Hodgkin’s lymphoma, head and neck tumors, and T-cell lymphoma. Objectives: This study aimed to determine the prevalence of EBV and its relation to the type of cancer in patients with head and neck tumors, which were treated in the years 2015 to 2016 at Shahid Rajaee Radiation Hospital in Babolsar. Methods: During one year, all patients with head and neck tumors were monitored, and finally, a total of 37 patients who had pathologically confirmed diagnoses were entered into the study after obtaining written informed consent. In this descriptive study, specific anti-EBV viral capsid antigen (VCA) immunoglobulin M (IgM) and IgG antibodies were evaluated using enzyme-linked immunosorbent assay (ELISA). Also, other patients’ information was obtained from their records. Results: The mean age of the patients was 59 years, and the number of men (70.23%) was higher than that of women (29.77%). Regarding the histopathology information and the frequency of tumors, most of the patients had squamous cell carcinoma (SCC) (73%) in the sites of the nasopharynx (27.02%) and pharynx (18.91%). The results of the ELISA test showed that IgG antibodies were positive in most of the patients (86.5 %). About the relation between the sites of the tumors and the IgG antibody, all patients (100%) with nasopharyngeal, tongue, and lips cancers were positive while they were the least in pharyngeal cancer (5.4%). Conclusions: This study showed that a significant number of patients with head and neck tumors (86.5%) were infected with this virus, which indicates that EBV as a carcinogenic agent in head and neck tumors has a high prevalence in our society and requires preventive and therapeutic actions.